2022
DOI: 10.1016/j.chembiol.2021.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Acriflavine, a clinically approved drug, inhibits SARS-CoV-2 and other betacoronaviruses

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 has been socially and economically devastating. Despite an unprecedented research effort and available vaccines, effective therapeutics are still missing to limit severe disease and mortality. Using high-throughput screening, we identify acriflavine (ACF) as a potent papain-like protease (PL pro ) inhibitor. NMR titrations and a co-crystal structure confirm that acriflavine blocks the PL pro catalytic pocket in an unexpect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…Acriflavine was recently reported to inhibit papain-like protease (PL pro ) from SARS-CoV-2, which contributed to drug-dependent suppression of viral replication. 7 Here, we explored another putative mechanism of the antiviral activity of acriflavine, i.e ., the inhibition of the interaction between the viral RBD domain of Spike protein and ACE2, the host receptor driving viral cell entry. Interaction between RBD and ACE2 in the presence of a vehicle (DMSO) was set to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Acriflavine was recently reported to inhibit papain-like protease (PL pro ) from SARS-CoV-2, which contributed to drug-dependent suppression of viral replication. 7 Here, we explored another putative mechanism of the antiviral activity of acriflavine, i.e ., the inhibition of the interaction between the viral RBD domain of Spike protein and ACE2, the host receptor driving viral cell entry. Interaction between RBD and ACE2 in the presence of a vehicle (DMSO) was set to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…A drug repurposing screening by Napolitano et al identified acriflavine ( 23 ) as a potent inhibitor of SARS-CoV-2 PL pro with in vivo antiviral efficacy. 82 Acriflavine ( 23 ) is a mixture of trypaflavine ( 24 ) and proflavine ( 25 ). 82 Acriflavine ( 23 ) inhibited PL pro with IC 50 values of 1.66 and 1.46 μM when RLRGG-AMC and ISG15-AMC were used as substrates, respectively ( Table 1 ).…”
Section: Sars-cov-2 Pl Pro Inhibitorsmentioning
confidence: 99%
“… 82 Acriflavine ( 23 ) is a mixture of trypaflavine ( 24 ) and proflavine ( 25 ). 82 Acriflavine ( 23 ) inhibited PL pro with IC 50 values of 1.66 and 1.46 μM when RLRGG-AMC and ISG15-AMC were used as substrates, respectively ( Table 1 ). Acriflavine ( 23 ) also inhibited the deubiquitylating activity of PL pro in gel-based assay, thus ruling out the potential fluorescence interference effect of acriflavine ( 23 ).…”
Section: Sars-cov-2 Pl Pro Inhibitorsmentioning
confidence: 99%
“…Acriflavine (ACF), published as a low µM (IC 50 ) PLpro inhibitor, was another drug identified with potential for repurposing. ACF showed promising antiviral activity in a number of different cell lines though it was unable to rival Remdesivir in blocking viral replication in the lungs of K18-ACE2 mice ( Napolitano et al, 2022 ). The published structure of PLpro in complex with a component of ACF, Proflavine (PDB 7NT4), indicates Proflavine is the active component inhibiting PLpro.…”
Section: Critical Assessment Of Examples Of Drug Repurposing “Hits”mentioning
confidence: 99%